Severe circumferential rectal ulcer associated with electric bidet toilet use - Takuro Nishiwaki; Kenichiro Nakachi; Shin Inoue; Takashi Ashikawa; Tomoyuki Funato; Natsuki Kawamitsu; Shigenobu Yoshimura; Hironobu Nagumo; So Nakaji; Koichi Homma (DEN Open)
Abstract A 66‐year‐old man presented to the gastroenterology department with anal pain. For >10 years, he had used an electric bidet toilet while defecating for >5 min at a time, because of constipation. Two weeks prior to his visit, he became aware of discomfort in his anal area and had used an enema 1 week previously. He had persistent diarrhea and began to use the electric bidet toilet at the highest water pressure for long periods. As a result, his anal pain worsened. A colonoscopy revealed circumferential inflammation and ulceration extending from the anal canal to the lower rectum. Approximately half of the Japanese population washes their anuses before and after defecation. Cleaning the anus after defecation using a bidet contributes to hand hygiene and local comfort, and may be effective against constipation. However, excessive bidet use may cause rectal disorders, such as rectal mucosal prolapse syndrome and solitary rectal ulcers. Herein, we report a rare case of a patient with advanced rectal ulceration caused by electric bidet toilet usage.